Beginning XSLT 2.0 From Novice to Professional - Tennison, Jeni.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2005)
This followup to Jeni Tennison's Beginning XSLT has been updated to accomodate the revised XSLT standard. Part one of this book introduces XML and XSLT at a comfortable pace, and gradually demonstrates techniques for generating HTML (plus other formats), from XML. In part two, Tennison applies theory to real-life XSLT capabilities—including generating graphics. Each chapter includes step-by-step examples (with code available online), plus review questions at the end, to help you grasp the discussed features. In fact, all of the examples and exercises revolve around an interesting common theme: making TV listings available online. This book lives up to its name, and will definitely take you from a novice to a professional, in no time!
Introducing XML -- Creating HTML from XML -- Templates -- Conditions -- Manipulating Atomic Values -- Variables and Parameters -- Paths and Sequences -- Result Trees -- Sorting and Grouping -- IDs, Keys, and Numbering -- Named Templates, Stylesheet Functions, and Recursion -- Building XSLT Applications -- Schemas -- Backwards Compatibility and Extensions -- Dynamic XSLT -- Creating SVG -- Interpreting RSS with XSLT.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems